Antibacterial waterproof coating for tiles and preparation process thereof
By mixing acrylate emulsion with a variety of additives and cement and other materials, the problems of poor adhesion of waterproof coatings and harmful to environmental health are solved, and efficient and environmentally friendly antibacterial waterproof coatings are achieved.
Patent Information
- Application Number
- CN202411526492.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing waterproof coatings are difficult to adhere directly to the surface of ceramic tile, and fluorine-containing waterproofing agents on the market are harmful to the environment and human health.
An antibacterial waterproof coating for ceramic tile was developed, and component A was formed by mixing the acrylate emulsion with a variety of additives, and mixing it with cement and filler to form component B, and mixing it in a certain proportion.
It achieves good adhesion and waterproofing properties of the paint on the surface of the ceramic tile, and has antibacterial, weather resistance, wear resistance, bonding properties and durability, and significantly improves the antibacterial effect under light.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coatings, in particular to an antibacterial waterproof coating for ceramic tiles and a preparation process thereof. Background Art
[0002] As time goes by, buildings and their materials will age and leak. Based on the above, applying waterproof coating can effectively improve its waterproof performance and aesthetics. However, some waterproof coatings are difficult to adhere directly to the surface of tiles. And the fluorine-containing waterproofing agents on the market will cause harm to the environment and human health. Therefore, we propose an antibacterial waterproof coating for tiles and its preparation process. Summary of the invention
[0003] The purpose of the present invention is to provide an antibacterial and waterproof coating for tiles and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an antibacterial waterproof coating for ceramic tiles comprises component A and component B, wherein component A comprises components: acrylic emulsion and additives; and component B is powder.
[0005] Furthermore, the powder material includes a mixture of two or more of cement, titanium frit, titanium dioxide, calcined talc, barium carbonate and heavy calcium.
[0006] Furthermore, the additives include a mixture of two or more of hydroxyethyl cellulose, cellulose ether, dispersant, wetting agent, defoamer, bactericide, defoaming agent, film-forming aid, mildewproofing agent, pH regulator, and thickener.
[0007] Further, component A includes the following components by mass: 90 to 95 parts of acrylic emulsion, 7.0 to 10.5 parts of additives;
[0008] The additives include the following components by weight: 5.5-6.0 parts of cellulose ether, 0.5-1.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.6-1.8 parts of film-forming aid, 0.1-0.3 parts of thickener, and 0.1-0.2 parts of wetting agent.
[0009] Furthermore, component B includes cement and a variety of fillers, and component B includes the following components by mass: 60 to 80 parts of cement, 7 to 12 parts of titanium frit, 30 to 50 parts of titanium dioxide, and 6 to 10 parts of barium carbonate.
[0010] Furthermore, the mass ratio of component A to component B is 1:(1-3).
[0011] A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0012] Mix the acrylic emulsion and the additives and disperse for 30 to 45 minutes to obtain component A;
[0013] Mixing cement, titanium frit, titanium dioxide and barium carbonate to obtain component B;
[0014] Mix component A and component B to obtain a coating.
[0015] Furthermore, the dispersion rotation speed is 600-800 r / min.
[0016] Further, the acrylic emulsion is prepared by the following process:
[0017] Long-chain alkyl trimethoxysilane, octamethylcyclotetrasiloxane, methyl triethoxysilane and vinyl triethoxysilane are mixed in deionized water, heated to 72-78° C., kept warm for 3-4 hours, cooled and neutralized to obtain an organosilicon seed emulsion;
[0018] Octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, allyl epoxy polyoxyethylene polyoxypropylene ether, and azobisisobutyronitrile were mixed in deionized water and homogenized for 30 minutes to obtain a pre-emulsion;
[0019] The pre-emulsion is reacted at a temperature of 70-75°C, stirred and the organosilicon seed emulsion is added within 2 hours, and the reaction is kept at this temperature for 3-4 hours to obtain an organosilicon-modified acrylate polymer;
[0020] Under the protection of nitrogen atmosphere, add dodecyl dimethyl tertiary amine, keep warm at 75-85°C for 3-4 hours; add glacial acetic acid and continue to react for 1-2 hours; and distill under reduced pressure to obtain a quaternary ammonium polymer;
[0021] An emulsifier is added and emulsified to obtain an acrylic emulsion.
[0022] Furthermore, the stirring speed is 300-400 r / min.
[0023] Furthermore, the organosilicon seed emulsion includes the following components by mass: 4 to 10 parts of long-chain alkyltrimethoxysilane, 14.5 to 17.0 parts of octamethylcyclotetrasiloxane, 1.5 to 3.0 parts of methyltriethoxysilane, and 3.5 to 4.5 parts of vinyltriethoxysilane, with a solid content of 50% to 60%.
[0024] Furthermore, the pre-emulsion includes the following components by mass: 2.5-3.0 parts of octadecyl methacrylate, 9.0-9.5 parts of butyl acrylate, 9.0-9.5 parts of methyl methacrylate, 2.0-5.5 parts of styrene, 0.3-0.5 parts of allyl epoxy polyoxyethylene polyoxypropylene ether, and 0.3-0.5 parts of azobisisobutyronitrile, and the solid content is 50%-60%.
[0025] Furthermore, the mass ratio of the pre-emulsion to the silicone seed emulsion is 10:(1.0-2.5).
[0026] Further, the mass ratio of allyl epoxy polyoxyethylene polyoxypropylene ether to dodecyl dimethyl tertiary amine is 1: (2.0-2.2);
[0027] The amount of glacial acetic acid used is 27% to 40% of the mass of dodecyl dimethyl tertiary amine;
[0028] The amount of emulsifier used is 0.5% to 10% of the mass of the pre-emulsion.
[0029] Furthermore, the solid content of the acrylic emulsion is 50% to 60%.
[0030] Furthermore, the long-chain alkyltrimethoxysilane is dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, or octadecyltrimethoxysilane.
[0031] Furthermore, the emulsifier is a mixture of octadecyltrimethylammonium chloride (1831), tri-fatty alcohol polyoxyethylene ether methyl silane (dispersant WA), and fatty alcohol and ethylene oxide condensate (Pingpingjia O-25), with a mass ratio of 2:1:1.
[0032] In the above technical scheme, the acrylate emulsion is a polymer emulsion made with acrylate compounds as the main polymer monomer, and as a coating, it has good water resistance, weather resistance, acid and alkali resistance and environmental protection characteristics after coating. On this basis, organic silicon (organic silicon seed emulsion) is added and grafted with acrylate polymer, which improves the waterproof performance of the prepared coating after coating, and also improves its softness, high and low temperature resistance, weather resistance, wear resistance, bonding performance and durability. Both acrylate compounds and organic silicon contain long-chain alkyl structures, which can further improve the water repellency of the coating and make it have good lubricity, antifouling and mechanical properties.
[0033] The polymerized monomer allyl epoxy polyoxyethylene polyoxypropylene ether is quaternized by using dodecyl dimethyl tertiary amine. The obtained quaternary ammonium salt has broad-spectrum antibacterial properties and is not easy to diffuse, thus giving the coating good antibacterial ability.
[0034] In the above technical scheme, acrylic emulsion and various additives are mixed to prepare organic liquid material as component A; cement and various fillers are used as component B. Two-component waterproof mortar is prepared according to a certain ratio. When it is used, component A and component B are mixed and stirred until there is no agglomeration. Construction begins after standing for 5 to 10 minutes. The construction temperature is suitable for 5 to 35°C. The coating amount is recommended to be 2.2kg / m2. After coating, it is dried and hardened for 48 to 72 hours.
[0035] Furthermore, the titanium dioxide is surface modified, and the surface modification process is as follows:
[0036] 1. Take N,N-dimethylformamide, add cyanuric chloride and quaternized chitosan at a temperature of 0-5°C, adjust the pH of the system to neutral, and react at a constant temperature for 5-8 hours; add isoxazole-3,5-diamine, heat to 40-50°C and react for 12-15 hours; heat to 80-90°C and continue to react for 15-20 hours; cool to 25-30°C, add 3,4-diacylhydrazide furazan, and react for 10-12 hours; freeze-dry to obtain an antibacterial compound;
[0037] 2. Mix titanium dioxide and alcohol aqueous solution, add epoxysiloxane, disperse for 5 to 10 minutes, and then reflux at 60 to 65° C. for 180 to 200 minutes; cool, filter, wash, and dry to obtain epoxidized titanium dioxide;
[0038] Mix epoxidized titanium dioxide and deionized water, stir for 15 to 20 minutes, add antibacterial compound, stir and react for 48 hours; filter, wash and dry to obtain modified titanium dioxide.
[0039] Furthermore, in step 1, the antibacterial compound is prepared from the following components by mass: 10 parts of cyanuric chloride, 10.4-11.5 parts of quaternized chitosan, 1.1-1.3 parts of isoxazole-3,5-diamine, and 10.1-15.2 parts of 3,4-diacylhydrazide furazan.
[0040] The ratio of cyanuric chloride to N,N-dimethylformamide is 5 g / 100 mL.
[0041] Further, in step 2, the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100: (0.5-1.0);
[0042] The ratio of titanium dioxide to alcohol aqueous solution is (8-10) g / 100 mL;
[0043] The concentration of the alcohol aqueous solution is 90v;
[0044] The ratio of epoxide titanium dioxide, antibacterial compound and deionized water is 100g: (0.5-1.0)g: (1.0-1.5)L.
[0045] In the above technical scheme, the hydroxyl group in the quaternized chitosan and the amino group at the end of isoxazole-3,5-diamine react with cyanuric chloride in turn to form oxazolyl chitosan quaternary ammonium salt. Its structure contains oxazole heterocycles, has good antibacterial activity, and can destroy its DNA structure by forming hydrogen bonds with DNA bases in proteins in bacteria, causing cell death; quaternized chitosan can enhance the stability of antibacterial compounds, and can change the permeability of bacterial cell membranes through quaternary ammonium salts, interact with the phospholipid bilayer of the cell membrane, destroy the integrity of the bacterial cell membrane, destroy the substance and energy exchange of the bacterial plasma membrane, leak substances inside the cell, denature proteins, and cause death. The combination of the two can further enhance the bactericidal effect and durability of the prepared coating.
[0046] The amide group in its structure is then reacted with the hydrazide group in 3,4-diazidazine furazan to obtain an oxazolyl chitosan quaternary ammonium salt having a hydrazide group, which is recorded as an antibacterial compound. While improving the antibacterial properties, it helps to improve its water resistance and adhesion.
[0047] By utilizing the reaction between the active group (amino group) and epoxy group in the structure of the antibacterial compound, the antibacterial compound is grafted onto the surface of titanium dioxide, which helps to improve the dispersibility of the powder in the acrylic emulsion. Titanium dioxide has a photocatalytic effect, and through the synergistic effect of photodynamics / photothermal dynamics, it can cooperate with the antibacterial compound to destroy the structure of the cell membrane, thereby quickly and efficiently inactivating bacteria.
[0048] When the modified titanium dioxide is used as a component in component B and blended with component A, the hydrazide groups on the surface of the modified titanium dioxide can react with the carbonyl groups in the acrylic emulsion under the acidic conditions provided by the acrylic emulsion, increasing the crosslinking degree of the coating system, which helps to improve the water resistance, adhesion and mechanical strength of the coating, and the product has antibacterial properties, further improving the bactericidal effect and durability of the coating. To ensure the above reaction process, the cement in component B is added last. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Quaternized chitosan: from Qingdao Bozhihuili Biotechnology Co., Ltd.
[0051] Titanium dioxide: FA-101, from Wuhan Fangyuan Titanium Dioxide Co., Ltd.;
[0052] Cement: PO4.5, from Southern Cement Co., Ltd.;
[0053] Titanium frit: 500 mesh crystal frit, sourced from Foshan Huage Ceramics Co., Ltd.
[0054] Barium carbonate: 300 mesh, sourced from Hengshui Huayao Technology Co., Ltd.;
[0055] Cellulose ether: from Shandong Heda Group Co., Ltd.
[0056] Dispersant TEGO Dispers 755W, wetting agent tego-822, from Tego Additives;
[0057] Defoamer BYK-028, from BYK Chemicals of Germany;
[0058] The film-forming aid is lauryl ester TEXANOL-12, which is from Eastman Chemical Co., Ltd., USA;
[0059] The thickener is glyceryl stearate, which comes from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0060] The emulsifier is a mixture of octadecyltrimethylammonium chloride (1831), tri-fatty alcohol polyoxyethylene ether methyl silane (dispersant WA), and fatty alcohol and ethylene oxide condensate (Pingpingjia O-25), with a mass ratio of 2:1:1;
[0061] The amount of glacial acetic acid used is 32% of the mass of dodecyl dimethyl tertiary amine; the amount of emulsifier used is 2% of the mass of the pre-emulsion; the concentration of the alcohol aqueous solution is 90v;
[0062] Embodiment 1: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0063] Step 1, dodecyltrimethoxysilane, octamethylcyclotetrasiloxane, methyltriethoxysilane, and vinyltriethoxysilane are mixed in deionized water, heated to 72°C, kept warm for reaction for 4 hours, cooled and neutralized to obtain an organosilicon seed emulsion; the organosilicon seed emulsion includes the following mass components: 4 parts of dodecyltrimethoxysilane, 17.0 parts of octamethylcyclotetrasiloxane, 3.0 parts of methyltriethoxysilane, and 3.5 parts of vinyltriethoxysilane, with a solid content of 50%;
[0064] Mix octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, allyl epoxy polyoxyethylene polyoxypropylene ether, and azobisisobutyronitrile in deionized water and homogenize for 30 minutes to obtain a pre-emulsion; the pre-emulsion includes the following components by weight: 2.5 parts of octadecyl methacrylate, 9.0 parts of butyl acrylate, 9.0 parts of methyl methacrylate, 2.0 parts of styrene, 0.3 parts of allyl epoxy polyoxyethylene polyoxypropylene ether, and 0.3 parts of azobisisobutyronitrile, and the solid content is 60%;
[0065] The pre-emulsion was stirred at 70°C and the organosilicon seed emulsion was added within 2 hours, and the reaction was kept warm for 3 hours to obtain an organosilicon-modified acrylate polymer; the mass ratio of the pre-emulsion to the organosilicon seed emulsion was 10:1;
[0066] Under the protection of nitrogen atmosphere, dodecyl dimethyl tertiary amine was added, and the reaction was kept at 75°C for 4 hours; glacial acetic acid was added, and the reaction was continued for 1 hour; vacuum distillation was performed to obtain a quaternary ammonium polymer; an emulsifier was added, emulsified, and the solid content was adjusted to obtain an acrylic emulsion with a solid content of 50%; the mass ratio of allyl epoxy polyoxyethylene polyoxypropylene ether to dodecyl dimethyl tertiary amine was 1:2;
[0067] 90 parts of acrylic emulsion and 10 parts of additives were mixed, and dispersed at a speed of 600 r / min for 45 minutes to obtain component A; the additives included the following components by weight: 6.0 parts of cellulose ether, 1.5 parts of dispersant, 0.5 parts of defoamer, 1.5 parts of film-forming aid, 0.3 parts of thickener, and 0.2 parts of wetting agent;
[0068] Step 2: Take N,N-dimethylformamide, add cyanuric chloride and quaternized chitosan at 5°C, adjust the pH of the system to neutral, and react at a constant temperature for 5 hours; add isoxazole-3,5-diamine, heat to 40°C and react for 15 hours; heat to 80°C and continue to react for 20 hours; cool to 25°C, add 3,4-diacylhydrazide furazan, and react for 12 hours; freeze-dry to obtain an antibacterial compound; the antibacterial compound is prepared from the following mass components: 10 parts of cyanuric chloride, 10.4 parts of quaternized chitosan, 1.1 parts of isoxazole-3,5-diamine, 10.1 parts of 3,4-diacylhydrazide furazan, and the ratio of cyanuric chloride to N,N-dimethylformamide is 5g / 100mL;
[0069] Mix titanium dioxide and alcohol aqueous solution, add epoxysiloxane, disperse for 5 minutes, and then reflux at 60°C for 200 minutes; cool, filter, wash, and dry to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:0.5; the ratio of titanium dioxide and alcohol aqueous solution is 8g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0070] Mix epoxidized titanium dioxide and deionized water, stir for 15 minutes, add antibacterial compound, stir and react for 48 hours; filter, wash and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, antibacterial compound and deionized water is 100g:0.5g:1L;
[0071] Mix 80 parts of cement, 12 parts of titanium frit, 30 parts of modified titanium dioxide, and 6 parts of barium carbonate to obtain component B;
[0072] Step 3: Mix component A and component B in a mass ratio of 1:3 to obtain a coating.
[0073] Embodiment 2: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0074] Step 1, hexadecyltrimethoxysilane, octamethylcyclotetrasiloxane, methyltriethoxysilane, and vinyltriethoxysilane are mixed in deionized water, heated to 75°C, kept warm for reaction for 3.5 hours, cooled and neutralized to obtain an organosilicon seed emulsion; the organosilicon seed emulsion includes the following components by mass: 7 parts of hexadecyltrimethoxysilane, 15.8 parts of octamethylcyclotetrasiloxane, 2.3 parts of methyltriethoxysilane, and 4 parts of vinyltriethoxysilane, with a solid content of 55%;
[0075] Mix octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, allyl epoxy polyoxyethylene polyoxypropylene ether, and azobisisobutyronitrile in deionized water and homogenize for 30 minutes to obtain a pre-emulsion; the pre-emulsion includes the following components by mass: 2.8 parts of octadecyl methacrylate, 9.2 parts of butyl acrylate, 9.2 parts of methyl methacrylate, 3.8 parts of styrene, 0.4 parts of allyl epoxy polyoxyethylene polyoxypropylene ether, and 0.4 parts of azobisisobutyronitrile, and the solid content is 55%;
[0076] The pre-emulsion was reacted at 72°C, stirred and the organosilicon seed emulsion was added within 2 hours, and the reaction was kept warm for 3.5 hours to obtain an organosilicon-modified acrylate polymer; the mass ratio of the pre-emulsion to the organosilicon seed emulsion was 10:1.8;
[0077] Under the protection of nitrogen atmosphere, dodecyl dimethyl tertiary amine was added, and the reaction was kept at 80°C for 3.5 hours; glacial acetic acid was added, and the reaction was continued for 1.5 hours; vacuum distillation was performed to obtain a quaternary ammonium polymer; an emulsifier was added, emulsified, and the solid content was adjusted to obtain an acrylic emulsion with a solid content of 55%; the mass ratio of allyl epoxy polyoxyethylene polyoxypropylene ether to dodecyl dimethyl tertiary amine was 1:2.1;
[0078] 92 parts of acrylic emulsion and 8 parts of additives were mixed, and dispersed at a speed of 700 r / min for 38 minutes to obtain component A; the additives included the following components by weight: 5.4 parts of cellulose ether, 1 part of dispersant, 0.3 parts of defoamer, 1.0 parts of film-forming aid, 0.2 parts of thickener, and 0.1 parts of wetting agent;
[0079] Step 2, take N, N-dimethylformamide, add cyanuric chloride and quaternized chitosan at a temperature of 2°C, adjust the pH of the system to neutral, and react at a constant temperature for 6.5 hours; add isoxazole-3,5-diamine and heat to 45°C for reaction for 14 hours; heat to 85°C and continue to react for 18 hours; cool to 28°C, add 3,4-diacylhydrazide furazan, and react for 11 hours; freeze-dry to obtain an antibacterial compound; the antibacterial compound is prepared from the following mass components: 10 parts of cyanuric chloride, 10.9 parts of quaternized chitosan, 1.2 parts of isoxazole-3,5-diamine, 12.6 parts of 3,4-diacylhydrazide furazan, and the ratio of cyanuric chloride to N, N-dimethylformamide is 5g / 100mL;
[0080] Mix titanium dioxide and alcohol aqueous solution, add epoxysiloxane, disperse for 8 minutes, and then reflux at 62°C for 190 minutes; cool, filter, wash, and dry to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:0.8; the ratio of titanium dioxide and alcohol aqueous solution is 9g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0081] Mix epoxidized titanium dioxide and deionized water, stir for 18 minutes, add antibacterial compound, stir and react for 48 hours; filter, wash and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, antibacterial compound and deionized water is 100g:0.8g:1.2L;
[0082] Mix 70 parts of cement, 10 parts of titanium frit, 40 parts of modified titanium dioxide, and 8 parts of barium carbonate to obtain component B;
[0083] Step 3: Mix component A and component B in a mass ratio of 1:2 to obtain a coating.
[0084] Embodiment 3: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0085] Step 1, octadecyltrimethoxysilane, octamethylcyclotetrasiloxane, methyltriethoxysilane, and vinyltriethoxysilane are mixed in deionized water, heated to 78°C, kept warm for reaction for 3 hours, cooled and neutralized to obtain an organosilicon seed emulsion; the organosilicon seed emulsion includes the following components by mass: 10 parts of octadecyltrimethoxysilane, 14.5 parts of octamethylcyclotetrasiloxane, 1.5 parts of methyltriethoxysilane, and 4.5 parts of vinyltriethoxysilane, with a solid content of 60%;
[0086] Mix octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, allyl epoxy polyoxyethylene polyoxypropylene ether, and azobisisobutyronitrile in deionized water and homogenize for 30 minutes to obtain a pre-emulsion; the pre-emulsion includes the following components by weight: 3.0 parts of octadecyl methacrylate, 9.5 parts of butyl acrylate, 9.5 parts of methyl methacrylate, 5.5 parts of styrene, 0.5 parts of allyl epoxy polyoxyethylene polyoxypropylene ether, and 0.5 parts of azobisisobutyronitrile, and the solid content is 60%;
[0087] The pre-emulsion was reacted at 75°C, stirred and the organosilicon seed emulsion was added within 2 hours, and the reaction was kept warm for 3 hours to obtain an organosilicon-modified acrylate polymer; the mass ratio of the pre-emulsion to the organosilicon seed emulsion was 10:2.5;
[0088] Under the protection of nitrogen atmosphere, dodecyl dimethyl tertiary amine was added, and the reaction was kept at 85°C for 3 hours; glacial acetic acid was added, and the reaction was continued for 2 hours; vacuum distillation was performed to obtain a quaternary ammonium polymer; an emulsifier was added, emulsified, and the solid content was adjusted to obtain an acrylic emulsion with a solid content of 60%; the mass ratio of allyl epoxy polyoxyethylene polyoxypropylene ether to dodecyl dimethyl tertiary amine was 1:2.2;
[0089] 95 parts of acrylic emulsion and 7.0 parts of additives were mixed and dispersed at a speed of 800 r / min for 30 minutes to obtain component A; the additives included the following components by weight: 5.5 parts of cellulose ether, 0.5 parts of dispersant, 0.1 parts of defoamer, 0.6 parts of film-forming aid, 0.1 parts of thickener, and 0.1 parts of wetting agent;
[0090] Step 2: Take N,N-dimethylformamide, add cyanuric chloride and quaternized chitosan at 0°C, adjust the pH of the system to neutral, and react at a constant temperature for 8 hours; add isoxazole-3,5-diamine, heat to 50°C and react for 12 hours; heat to 90°C and continue to react for 15 hours; cool to 30°C, add 3,4-diacylhydrazide furazan, and react for 10 hours; freeze-dry to obtain an antibacterial compound; the antibacterial compound is prepared from the following mass components: 10 parts of cyanuric chloride, 11.5 parts of quaternized chitosan, 1.3 parts of isoxazole-3,5-diamine, 15.1 parts of 3,4-diacylhydrazide furazan, and the ratio of cyanuric chloride to N,N-dimethylformamide is 5g / 100mL;
[0091] Mix titanium dioxide and alcohol aqueous solution, add epoxysiloxane, disperse for 10 minutes, and then reflux at 65°C for 180 minutes; cool, filter, wash, and dry to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:1; the ratio of titanium dioxide and alcohol aqueous solution is 10g / 100mL;
[0092] Mix epoxidized titanium dioxide and deionized water, stir for 20 minutes, add antibacterial compound, stir and react for 48 hours; filter, wash and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, antibacterial compound and deionized water is 100g:1.0g:1.5L;
[0093] Mix 60 parts of cement, 12 parts of titanium frit, 50 parts of modified titanium dioxide, and 10 parts of barium carbonate to obtain component B;
[0094] Step 3: Mix component A and component B in a mass ratio of 1:1 to obtain a coating.
[0095] Comparative Example 1: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0096] Step 2, titanium dioxide and alcohol aqueous solution are mixed, epoxysiloxane is added, dispersed for 5 minutes, and refluxed at 60°C for 200 minutes; cooled, filtered, washed, and dried to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:0.5; the ratio of titanium dioxide and alcohol aqueous solution is 8g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0097] Mix epoxidized titanium dioxide and deionized water, stir for 15 minutes, add quaternized chitosan, stir and react for 48 hours; add 3,4-diacylhydrazide furazan, react for 12 hours; filter, wash and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, quaternized chitosan, 3,4-diacylhydrazide furazan and deionized water is 100g:0.5g:0.18g:1L;
[0098] Mix 80 parts of cement, 12 parts of titanium frit, 30 parts of modified titanium dioxide, and 6 parts of barium carbonate to obtain component B;
[0099] Step 1 and step 3 are the same as those in Example 1 to obtain a coating.
[0100] Comparative Example 2: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0101] Step 2, titanium dioxide and alcohol aqueous solution are mixed, epoxysiloxane is added, dispersed for 5 minutes, and refluxed at 60°C for 200 minutes; cooled, filtered, washed, and dried to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:0.5; the ratio of titanium dioxide and alcohol aqueous solution is 8g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0102] Mix epoxidized titanium dioxide and deionized water, stir for 15 minutes, add quaternized chitosan, and stir for 48 hours; filter, wash, and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, quaternized chitosan, and deionized water is 100g:0.5g:1L;
[0103] Mix 80 parts of cement, 12 parts of titanium frit, 30 parts of modified titanium dioxide, and 6 parts of barium carbonate to obtain component B;
[0104] Step 1 and step 3 are the same as those in Example 1 to obtain a coating.
[0105] Comparative Example 3: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0106] Step 2, titanium dioxide and alcohol aqueous solution are mixed, epoxysiloxane is added, dispersed for 5 minutes, and refluxed at 60°C for 200 minutes; cooled, filtered, washed, and dried to obtain epoxidized titanium dioxide; the mass ratio of titanium dioxide and epoxysiloxane KH-560 is 100:0.5; the ratio of titanium dioxide and alcohol aqueous solution is 8g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0107] Mix epoxidized titanium dioxide and deionized water, stir for 15 minutes, add isoxazole-3,5-diamine, and stir for 48 hours; filter, wash, and dry to obtain modified titanium dioxide; the ratio of epoxidized titanium dioxide, isoxazole-3,5-diamine, and deionized water is 100g:0.5g:1L;
[0108] Mix 80 parts of cement, 12 parts of titanium frit, 30 parts of modified titanium dioxide, and 6 parts of barium carbonate to obtain component B;
[0109] Step 1 and step 3 are the same as those in Example 1 to obtain a coating.
[0110] Comparative Example 4: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0111] Step 2, titanium dioxide and alcohol aqueous solution are mixed, siloxane is added, dispersed for 5 minutes, and then refluxed at 60°C for 200 minutes; cooled, filtered, washed, and dried to obtain modified titanium dioxide; the mass ratio of titanium dioxide and siloxane KH-550 is 100:0.5; the ratio of titanium dioxide and alcohol aqueous solution is 8g / 100mL; the concentration of alcohol aqueous solution is 90v;
[0112] Mix 80 parts of cement, 12 parts of titanium frit, 30 parts of modified titanium dioxide, and 6 parts of barium carbonate to obtain component B;
[0113] Step 1 and step 3 are the same as those in Example 1 to obtain a coating.
[0114] Comparative Example 5: A preparation process of an antibacterial waterproof coating for tiles, comprising the following processes:
[0115] Step 1, octamethylcyclotetrasiloxane, methyltriethoxysilane, and vinyltriethoxysilane are mixed in deionized water, heated to 72° C., kept warm for reaction for 4 hours, cooled and neutralized to obtain an organosilicon seed emulsion; the organosilicon seed emulsion comprises the following components by mass: 17.0 parts of octamethylcyclotetrasiloxane, 3.0 parts of methyltriethoxysilane, and 3.5 parts of vinyltriethoxysilane, with a solid content of 50%;
[0116] Butyl acrylate, methyl methacrylate, styrene, acryloyloxyethyl dimethyl ethyl ammonium bromide, and azobisisobutyronitrile are mixed in deionized water and homogenized for 30 minutes to obtain a pre-emulsion; the pre-emulsion includes the following components by mass: 9.0 parts of butyl acrylate, 9.7 parts of methyl methacrylate, 2.0 parts of styrene, 0.3 parts of acryloyloxyethyl dimethyl ethyl ammonium bromide, and 0.3 parts of azobisisobutyronitrile, and the solid content is 60%;
[0117] The pre-emulsion was stirred at 70°C and the organosilicon seed emulsion was added within 2 hours, and the reaction was kept warm for 3 hours to obtain an organosilicon-modified acrylate polymer; the mass ratio of the pre-emulsion to the organosilicon seed emulsion was 10:1; an emulsifier was added, emulsified, and the solid content was adjusted to obtain an acrylate emulsion with a solid content of 50%;
[0118] 90 parts of acrylic emulsion and 10 parts of additives were mixed, and dispersed at a speed of 600 r / min for 45 minutes to obtain component A; the additives included the following components by weight: 6.0 parts of cellulose ether, 1.5 parts of dispersant, 0.5 parts of defoamer, 1.5 parts of film-forming aid, 0.3 parts of thickener, and 0.2 parts of wetting agent;
[0119] Step 2 and step 3 are the same as those in Comparative Example 4 to obtain a coating.
[0120] Experiment: Take the coatings obtained in Examples 1-3 and Comparative Examples 1-5, prepare samples, test their properties respectively and record the test results:
[0121] Bonding strength test: The pull-out method is used to test the bonding strength of the coating sample on the flat glazed ceramic tile. After mixing component A and component B, let it stand for 10 minutes. The coating amount is 2.2kg / m2, the ambient temperature is 25℃, and it is dried for 72 hours after coating.
[0122] Waterproof performance test: Use an electronic balance to detect the initial mass of the sample. After soaking in tap water for 48 hours, quickly take it out and wipe off the surface moisture, weigh it again, and calculate the water absorption rate as the test result;
[0123] Mechanical properties test: GB / T 16777 was used as the reference standard to test the tensile properties of the specimens at a tensile rate of 200 mm / min.
[0124] Antibacterial performance test: GB / T 21866 was used as the reference standard, Staphylococcus aureus (S. aureus, 1.8×10 7 CFU / mL) and Escherichia coli (E.coli, 1.6×10 7 CFU / mL) was used as the test bacteria, and the 24-hour antibacterial rate of the samples was tested under light-proof conditions and light conditions, respectively. A 500W xenon lamp was used for illumination, with a wavelength of 420-700nm and an illumination time of 30min.
[0125] Table 1
[0126]
[0127] Table 2
[0128]
[0129] According to the data in the above table, we can clearly draw the following conclusions:
[0130] The coatings obtained in Examples 1-3 were compared with the coating films obtained in Comparative Examples 1-5. The test results show that:
[0131] Compared with the comparative example, the coatings obtained in Examples 1-3 have higher bonding strength, antibacterial rate, tensile strength data and lower water absorption rate data after coating and drying, and the antibacterial rate data of the coatings after light exposure is higher. This fully demonstrates that the present invention achieves the improvement of the antibacterial and waterproof properties of the coating, improves its mechanical properties and bonding properties, and has a better antibacterial effect under visible light.
[0132] Compared with Example 1, the modified titanium dioxide in Comparative Example 1 is prepared from epoxidized titanium dioxide, quaternized chitosan, and 3,4-dihydrazide furazan; the modified titanium dioxide in Comparative Example 2 is prepared from epoxidized titanium dioxide and quaternized chitosan; the modified titanium dioxide in Comparative Example 3 is prepared from epoxidized titanium dioxide and isoxazole-3,5-diamine; the modified titanium dioxide in Comparative Example 4 is KH-550 modified titanium dioxide; compared with Comparative Example 4, there is no long-chain alkyl and quaternary ammonium salt in Comparative Example 5. After the coatings obtained in Comparative Examples 1-5 are applied and dried, the bonding strength, antibacterial rate, and tensile strength data decrease, and the water absorption rate data increases. It can be seen that the setting of the coating components and their preparation process of the present invention can promote the comprehensive improvement of their antibacterial, waterproof, mechanical and bonding properties, and the antibacterial effect after illumination is better.
[0133] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A preparation process of an antibacterial waterproof coating for tiles, characterized in that: Including the following processes: Mix the acrylic emulsion and the additives and disperse for 30 to 45 minutes to obtain component A; Mixing cement, titanium frit, titanium dioxide and barium carbonate to obtain component B; Mixing component A and component B to obtain a coating; The acrylic emulsion is prepared by the following process: Long-chain alkyl trimethoxysilane, octamethylcyclotetrasiloxane, methyl triethoxysilane and vinyl triethoxysilane are mixed in deionized water, heated to 72-78° C., and kept warm for 3-4 hours to obtain an organosilicon seed emulsion; Octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, allyl epoxy polyoxyethylene polyoxypropylene ether, and azobisisobutyronitrile were mixed in deionized water and homogenized for 30 minutes to obtain a pre-emulsion; The pre-emulsion is reacted at a temperature of 70-75°C, stirred and the organosilicon seed emulsion is added within 2 hours, and the reaction is kept at this temperature for 3-4 hours to obtain an organosilicon-modified acrylate polymer; Under the protection of nitrogen atmosphere, add dodecyl dimethyl tertiary amine, keep warm at 75-85°C for 3-4 hours; add glacial acetic acid, continue to react for 1-2 hours to obtain a quaternary ammonium polymer; adding an emulsifier, emulsifying, and obtaining an acrylic emulsion; The titanium dioxide is surface modified, and the process of surface modification is as follows: Take N,N-dimethylformamide, add cyanuric chloride and quaternized chitosan at a temperature of 0 to 5°C, adjust the pH of the system to neutral, and react at a constant temperature for 5 to 8 hours; add isoxazole-3,5-diamine, raise the temperature to 40 to 50°C, react for 12 to 15 hours; raise the temperature to 80 to 90°C, continue to react for 15 to 20 hours; lower the temperature to 25 to 30°C, add 3,4-diacylhydrazide furazan, react for 10 to 12 hours, and obtain an antibacterial compound; Mix titanium dioxide and alcohol aqueous solution, add epoxysiloxane, disperse for 5 to 10 minutes, and then reflux at 60 to 65° C. for 180 to 200 minutes to obtain epoxidized titanium dioxide; Mix epoxidized titanium dioxide and deionized water, stir for 15 to 20 minutes, add the antibacterial compound, stir and react for 48 hours to obtain modified titanium dioxide; The coating comprises component A and component B, wherein component A comprises components: acrylic emulsion and additives; The component B is a powder, comprising the following components by mass: 60-80 parts of cement, 7-12 parts of titanium frit, 30-50 parts of modified titanium dioxide, and 6-10 parts of barium carbonate; the component A comprises the following components by mass: 90-95 parts of acrylic emulsion and 7.0-10.5 parts of additives; The additive comprises the following components by weight: 5.5-6.0 parts of cellulose ether, 0.5-1.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.6-1.8 parts of film-forming aid, 0.1-0.3 parts of thickener, and 0.1-0.2 parts of wetting agent; The mass ratio of component A to component B is 1:(1-3).
2. The preparation process of an antibacterial waterproof coating for tiles according to claim 1, characterized in that: The antibacterial compound is prepared from the following components by mass: 10 parts of cyanuric chloride, 10.4-11.5 parts of quaternized chitosan, 1.1-1.3 parts of isoxazole-3,5-diamine, and 10.1-15.2 parts of 3,4-diacylhydrazide furazan.
3. The preparation process of an antibacterial waterproof coating for tiles according to claim 1, characterized in that: The organosilicon seed emulsion comprises the following components by weight: 4 to 10 parts of long-chain alkyl trimethoxysilane, 14.5 to 17.0 parts of octamethylcyclotetrasiloxane, 1.5 to 3.0 parts of methyl triethoxysilane, and 3.5 to 4.5 parts of vinyl triethoxysilane.
4. The preparation process of an antibacterial waterproof coating for tiles according to claim 1, characterized in that: The pre-emulsion comprises the following components by mass: 2.5-3.0 parts of octadecyl methacrylate, 9.0-9.5 parts of butyl acrylate, 9.0-9.5 parts of methyl methacrylate, 2.0-5.5 parts of styrene, 0.3-0.5 parts of allyl epoxy polyoxyethylene polyoxypropylene ether, and 0.3-0.5 parts of azobisisobutyronitrile.
5. The preparation process of an antibacterial waterproof coating for tiles according to claim 1, characterized in that: The mass ratio of the pre-emulsion to the organosilicon seed emulsion is 10:(1.0-2.5); the mass ratio of the allyl epoxy polyoxyethylene polyoxypropylene ether to dodecyl dimethyl tertiary amine is 1:(2.0-2.2).
6. An antibacterial and waterproof coating for tiles prepared according to the preparation process according to any one of claims 1 to 5.
Citation Information
Patent Citations
Water-based weather-proof stain-proof thermal reflective insulation coating and preparation method thereof
CN104250498A
Stain-proofing coating and method for producing the same
JP2005036045A